"Privacy by default" and active "informed consent" by layers: Essential measures to protect ICT users' privacy. Issue 2 (9th May 2016) - Noain-Sánchez, Amaya
Abstract : Purpose: The purpose of this paper is to lay out an approach to addressing the problem of privacy protection in the global digital environment based on the importance that information has to improve users' informational self-determination. Following this reasoning, this paper focuses on the suitable way to provide user with the correct amount of information they may need to maintain a desirable grade of autonomy as far as their privacy protection is concerned and decide whether or not to put their personal data on the internet. Design/methodology/approach: The authors arrive at this point in their analysis by qualitative discourse analysis of the most relevant scientific papers and dossiers relating to privacy protection. Findings: The goal of this paper is twofold. The first is to illustrate the importance of privacy by default and informed consent working together to protect information and communication technology (ICT) users' privacy. The second goal is to develop a suitable way to administrate the mentioned "informed consent" to users. Originality/value: To fulfil this purpose, the authors present a new concept of informed consent: active "informed consent" or "Opt-in" model by layers. "Opt-in" regimens have already been used with cookies but never with 2.0 applications, as, for instance, social network sites (SNS).